National and international developments in technology – Trends, patterns and implications for policy - Georg Koopmann; Felix Münnich (Hamburg Institute of International Economics (HWWA), 1999)
Declining R&D intensities at the national level coincide with growing international technological links. Deviations of individual OECD countries from the average R&D intensity reflect differences in industry structure as well as in sectoral R&D intensity. At the same time, the sectoral distribution of R&D expenditure varies substantially less across countries than do the respective growth rates. Foreign direct investment (FDI) is the most important vehicle for the exploitation of ?home-grown? technology abroad. FDI frequently also entails the generation of knowledge abroad in own R&D facilities the nature of which increasingly shifts from adaptation to innovation development and knowledge-seeking. In addition, international technological collaboration via in- and outsourcing and inter-company alliances is gaining growing significance. The policy challenges posed by technological internationalisation include the provision of better market access, more effective patent protection and competitive regimes, as well as the promotion of clustering and networking and international cooperation. – – Sinkende FuE-Intensitäten auf der nationalen Ebene gehen mit einer wachsenden internationalen Technologieverflechtung einher. In den Abweichungen einzelner OECDLänder von der durchschnittlichen FuE-Intensität spiegeln sich Unterschiede in der Industriestruktur und in der sektoralen FuE-Intensität wider. Gleichzeitig unterscheiden sich die Länder weniger in der sektoralen Verteilung der FuE-Ausgaben als in den Zuwachsraten. Direktinvestitionen sind das bedeutendste Vehikel der Verwertung inländischer Technologie im Ausland. Sie führen häufig auch zur Erzeugung neuen Wissens in ausländischen FuE-Einrichtungen, die verstärkt eigene FuE statt reiner Anpassungsentwicklung betreiben und ausländisches Wissen suchen. Neben Verwertung und Erzeugung gewinnt die internationale technologische Kooperation via In- und Outsourcing und Allianzen zwischen Unternehmen wachsende Bedeutung. Die politischen Herausforderungen der technologischen Internationalisierung schließen einen verbesserten Marktzugang, effizienteren Patent- und Wettbewerbsschutz sowie die Förderung der Cluster- und Netzwerkbildung und internationalen Kooperation ein.
Keywords: 330; Industrielle Forschung; Industrieller Strukturwandel; Technologie; Innovation; Forschungskooperation; Internationale Unternehmenskooperation; Forschungs- und Technologiepolitik; Welt; G5-Staaten; Deutschland; Vereinigte Staaten